ETIKA DAN BUDAYA ORGANISASI: PERAN KEPEMIMPINAN DALAM MEMBANGUN LINGKUNGAN KERJA BERINTEGRITAS - Adelia Yunita Setyadi, Faridhatun Nafi’ah, Tara Umi Nur Wakhidatun, Abida Intan Nur’aini, Rauly Sija (PT Wahana Global Education, 2025)
Ethics and organizational culture play a vital role in influencing individual actions and driving the overall performance of an organization. Organizational ethics pertain to moral guidelines that inform decision-making processes, while organizational culture encompasses the collective values, norms, and traditions embraced by its members. This paper examines how ethics and culture intersect within organizations and their effects on employee integrity, efficiency, and job satisfaction. Specifically, this article will highlight the role of leadership in shaping and maintaining a healthy and ethical organizational culture. Through a qualitative lens with a literature review approach, the study finds that organizations with a well-established ethical culture foster a supportive work atmosphere, mitigate internal disputes, and build stronger trust and employee commitment. These insights emphasize the crucial role of ethical leadership and transparent communication in cultivating a culture grounded in moral principles for the long-term sustainability of the organization.